The Scars of Project 459 : The Environmental Story of the Lake of the Ozarks - Angel, Traci (Book collections on Project MUSE., 2014)
Traci Angel is a writer and editor who lives in Kansas City, Missouri. She is a former health reporter for the Jackson Hole News & Guide and covered regional topics while a reporter for the Associated Press and editor at St. Louis Magazine . She has been following the environmental situation of the Lake of the Ozarks for several years.